The Early Effects of COVID-19 on Plastic Surgery Residency Training: The University of Washington Experience. Issue 2 (August 2020) - Cho, Daniel Y.; Yu, Jenny L.; Um, Grace T.; Beck, Christina M.; Vedder, Nicholas B.; Friedrich, Jeffrey B.
Abstract : Summary: Plastic surgeons have the unique perspective of working with all types of patients and care teams from almost all specialties in surgery and medicine, which creates unique challenges in times of distress. As the initial epicenter of coronavirus disease 2019 cases in the United States, the University of Washington program was required to rapidly develop strategies to deal with the escalating crisis. All aspects of the program were affected, including the need to triage the urgency of plastic surgery care, safe staffing of plastic surgery teams, and the role of plastic surgery in the greater hospital community. In addition, as a residency training program, limiting the impact of resident education and maintaining a sense of community and connection among members of the program developed into important considerations. The authors hope that the narrative of their experience will provide insight into the decisions made in the University of Washington health care system but also remind others that they are not alone in dealing with the challenges of this pandemic.